Evaluation of Double Cross on Growth and Production of Cayenne Pepper (Capsicum frutescens L.) - Muh Farid BDR; Yunus Musa; Azmi Nur Karimah Amas; Muh. Fuad Anshori; Nirwansyah Amier (Agrotech Journal, 2023)
Cayenne pepper is one of the horticultural commodities with high economic value in Indonesia. In addition, this plant also never runs out of enthusiast because almost everyone needs it. Therefore, the fulfillment of this demand must be supported by the availability of sufficient cayenne pepper in Indonesia. This research aims to obtain better diversity in the results of double cross and three way cross than their parents, to obtain characters with good genetic parameters in predicting the results of double cross and three way cross crosses, and to obtain hybrid combinations of cayenne pepper resulting from double cross and three way cross which has purple fruit properties. The results of the evaluation of crosses showed that all cross-evaluation characters had a high heritability predictive value and were followed by high genetic diversity in the characters of plant height, dichotomous height, plant habitus, flowering age, harvesting age, fruit weight, fruit length, fruit diameter, fruit stalks length, and yield.